MOTIVASI YANG MENDASARI LOYALITAS PEMBACA HARIAN JOGLOSEMAR DI KECAMATAN KARANGMALANG SRAGEN - Bedjo Sukarno, Nurnawati H.H, Tetuko Widiantoro, (Solidaritas, 2018)
ABSTRACKÂ Located in District Karangmalang Sragen regency, this research uses the theory proposed by Blummer that is the motive of media usage is the cognitive orientation that is information needs, diversi is the need for entertainment, and raises the personal identity of the reader. Technique of collecting data obtained by purposive sampling through interview with informant, observation and document. The data validity test is obtained by triangulation of data, as well as data analysis technique using interactive modeling technique by Miles and Huberman.The need for information is a motivation that encourages the readers loyalty and puts Daily JOGLOSEMAR as a medium to meet the needs of information and news. Daily JOGLOSEMAR also provide entertainment, it can be a means of relaxation of saturation and give pleasure to the reader. Harian JOGLOSEMAR also took part in growing the personal identity of its readers. With the articles presented, readers can obtain information to build their self-concept, world view, and views about human nature.Â Keywords: loyalty, motivation, reader, newspaper